Poverty Review in Novel Padang Bulan Karya Andrea Hirata - Saroyan Joat, Oktavianus (Udayana Journal of Social Sciences and Humanities; Vol 3 No 2 (2019): UJoSSH, September 2019DO - 10.24843/UJoSSH.2019.v03.i02.p07, 2019)
This research describes the poverty problem described in the Padang Bulan novel by Andrea Hinata through the social life of the Belitung Malay community. This research aims to reveal various forms of the social life of the community and deconstruct the discourse hidden behind the social life of the society that the author describes according to the social life of the Belitung Malay community. According to deconstruction theory, power and knowledge relations used in this research to analyze data through the sociological approach of literature. This research uses qualitative methods, especially literature studies that are commonly applied in the study of literary texts. This study found that poverty described by the author towards Belitung Malay society was very clear showing the social reality experienced by most Indonesian people and storing various relations of power and knowledge through various discourses played by the capitalists to benefit without regard to the working class, namely society.